Ageing increases risk of lower eyelid malposition after primary orbital fracture reconstruction - Rajantie Hanna; Nikunen Matti; Raj Rahul; Snäll Johannna; Thorén Hanna (Elsevier, 2022)
Lower eyelid malposition (LEM) is a common sequela after orbital fracture reconstruction. This study aimed to analyse the development of LEM, specifically ectropion and entropion, following primary orbital fracture reconstruction, to identify predictive factors for LEM, and to assess the effect of the eyelid complication on patients' daily lives. The retrospective cohort comprised patients who had undergone orbital floor and/or medial wall fracture reconstruction for recent trauma. Demographics, fracture type and site, surgery and implant-related variables, follow-up time and number of visits, type and severity of LEM, subsequent surgical correction, and patient satisfaction, were analysed. The overall occurrence of LEM was 8%, with ectropion in 6% and entropion in 2% of patients. Older age, complex fractures, transcutaneous approaches, preoperative traumatic lower lid wounds, and implant material were associated with the development of LEM. Of all patients, 3% needed surgical correction of LEM. Six of the 13 patients (46%) who developed LEM required surgical correction. The transconjunctival approach and patient-specific implants should be preferred, especially in elderly patients and those with more complex fractures. LEM often requires subsequent surgical correction, and the treatment period is substantially prolonged, with multiple extra visits to the clinic.